Desenvolvimento de métodos de extração para análise de 17α-etinilestradiol e Bisfenol-A em amostras biológicas por cromatografia líquida de alta eficiência - SILVA, Lúcia Guêzo Almeida da (2012)
This work aimed to develop an efficient extraction method to enable the identification and quantification of two compounds that are in increasing scientific study, Bisphenol-A (BPA) and 17α-ethinylestradiol (EE2) in tadpoles organisms used in ecotoxicological tests . For this, the technique used was Liquid High Efficiency Chromatography (HPLC). BPA is a widely used substance during industrial processes as a monomer in the production of polycarbonates, polymers, epoxy resins and unsaturated polyester-styrene resins, as well as being used as an inner coating on aluminum cans used in beverages such as dental sealants as Antioxidant, among others. EE2 is an estrogen hormone widely used in birth control pills that has effects very similar to those of BPA with the potential for hormonal disorders that can cause adverse effects on the health of animals and humans. For the optimization of the procedures, 4 extraction tests were performed, which varied according to studies reported in the literature. Of the procedures performed, the best recovery was the test 4 that obtained 52% for the BPA and 32% for the EE2, being therefore acceptable only for BPA analysis. This test was carried out in four stages using solid phase dispersion with hexane and liquid-liquid extraction with acetonitrile, ending the extraction with the total evaporation and restitution of the sample with 2 ml of acetonitrile. Animals from ecotoxicological tests with BPA were analyzed and submitted to the procedures described in test 4, where they did not present the presence of the compound.